Diáspora como movimento social: implicações para a análise dos movimentos sociais de combate ao racismo - Marilise L.M. dos Reis (Ciências Sociais Unisinos)
This article aims to deal with some discussions that are being developed in some contemporary studies on social movements, which search to articulate categories of Postcolonial studies to the thematic of social movements. Thus, it is discussed the possibility of thinking the social movements of racism combat, and the politics actions articulated to them, from the concepts of "diaspora" and "Black Atlantic", and of a theoretical orientation based on Postcolonials and cultural studies, considering their subsequent contributions to the networks theory of social movements.